Mediasi Komitmen Kerja pada Hubungan antara Budaya Organisasi terhadap Kinerja Guru Era Merdeka Belajar - Feriawan Efendi; Sri Wulan Ambarwati; Febranti Putri Navion (Jurnal Paedagogy, 2023)
This study aims to analyze the influence of organizational culture on teacher performance, the influence of organizational culture on work commitment, the influence of work commitment on teacher performance, and the influence of organizational culture on teacher performance in the era of independent learning mediated by work commitment. This study used a survey method with a quantitative approach. The sample for this study consisted of 88 teachers from the Senior High School of the Program Sekolah Penggerak (PSP) in the Education Branch of Blitar City. The instrument used was a questionnaire distributed to respondents online through Google Forms. Then, the data were analyzed using descriptive statistics and Partial Least Squares (PLS). The results showed a positive and significant influence of organizational culture on teacher performance in the era of independent learning, a positive and significant influence of organizational culture on work commitment, no significant influence of work commitment on teacher performance in the era of independent learning, and no mediating effect of work commitment and no significant influence of organizational culture on teacher performance in the era of independent learning.